2019
DOI: 10.5811/westjem.2019.1.41375
|View full text |Cite
|
Sign up to set email alerts
|

Radiograph Interpretation Discrepancies in a Community Hospital Emergency Department

Abstract: Introduction In many hospitals, off-hours emergency department (ED) radiographs are not read by a radiologist until the following morning and are instead interpreted by the emergency physician (EP) at the time of service. Studies have found conflicting results regarding the radiographic interpretation discrepancies between EPs and trained radiologists. The aim of this study was to identify the number of radiologic interpretation discrepancies between EPs and radiologists in a community ED setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
7
1
1
Order By: Relevance
“…Instead, the initial interpretation was conducted by a senior emergency physician, followed by a thorough review by a trained emergency medicine resident. However, it is worth noting that in previous studies, investigators have noted that the incidence of clinically significant discrepancies in radiographs interpreted by emergency physicians is not lower than that of those interpreted by radiologists [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the initial interpretation was conducted by a senior emergency physician, followed by a thorough review by a trained emergency medicine resident. However, it is worth noting that in previous studies, investigators have noted that the incidence of clinically significant discrepancies in radiographs interpreted by emergency physicians is not lower than that of those interpreted by radiologists [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Missed fractures represent up to 80% of diagnostic errors in the ED [ 10 ], and it frequently lead to legal problems in medicine [ 11 ]. Given the radiology workforce shortage and emergent clinical situations, physicians in the ED should often make management decisions before radiologic reports become available, especially considering plain radiographs [ 12 , 13 ]. In our study, the cervical spine was the most common location of missed fractures, showing consistency with various studies that have reported that plain radiography may lead to miss more than 50% of cervical spine fractures for reasons including inadequate cervical spine series (e.g., lateral view only, non-visualization of C7-T1) and misreading of plain radiographies with or without adequate standard series [ 10 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RRDs were categorized on a scale from 1‒4 according to the patients’ disposition and outcomes [ 2 , 16 ]. Category 1 was a minor discrepancy with no additional immediate action needed.…”
Section: Methodsmentioning
confidence: 99%
“…There have been numerous studies on resident-to-attending radiology report discrepancies (RRDs). Most studies have focused on discrepancy rates between preliminary and finalized radiology reports and have underscored the diagnostic imaging modalities in which RRDs are frequently found [ 2 6 ]. Several studies have emphasized the importance of resident training level and attending radiologists reading after hours [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%